Variation in Growth, Physiology, Yield, and Quality of Wheat under the Application of Different Zinc Coated Formulations - Qudsia Nazir; Xiukang Wang; Azhar Hussain; Allah Ditta; Ayesha Aimen; Ifra Saleem; Muhammad Naveed; Tariq Aziz; Adnan Mustafa; Nalun Panpluem (Applied Sciences, 2021)
Zinc (Zn) is critical for the activity of many enzymes including involved photosynthetic CO2 fixation and indirectly involved in the production of growth hormones and internode elongation in crop plants. In this regard, a field experiment was conducted to investigate the comparative effectiveness of the Zn blended, Zn coated and bio-activated Zn coated urea on the growth, physiological, yield, and quality of wheat. Three types of urea were prepared including bio-activated Zn coated, Zn coated and Zn blended urea. The bio-activated Zn coated urea was prepared by inoculating the powdered organic material with Zn solubilizing bacterium (Bacillus sp. AZ6) and then this material was mixed with ZnO. This bioactive Zn was coated on urea at the rate to formulate 1.5% bio-activated Zn coated urea. Moreover, Zn blended urea was prepared by mixing powder ZnO with urea while Zn coated urea with 1.5% Zn was prepared by mixing ZnO and urea under proper moisture conditions to ensure proper coating. In results, growth parameters were significantly increased with the application of bio-activated Zn coated urea as compared to other urea formulations and the control. The same treatment caused the maximum increase in quality parameters like oil contents (55%), protein (30%), and N concentration (30%) as compared to the control. In conclusion, the application of 1.5% bio-activated Zn coated urea was highly effective in enhancing the growth, physiological, yield, and quality parameters of wheat.